2017
DOI: 10.1038/s41598-017-03929-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Spatial and Temporal Patterns of Observed Ground-level Ozone in China

Abstract: Elevated ground-level ozone (O3), which is an important aspect of air quality related to public health, has been causing increasing concern. This study investigated the spatiotemporal distribution of ground-level O3 concentrations in China using a dataset from the Chinese national air quality monitoring network during 2013–2015. This research analyzed the diurnal, monthly and yearly variation of O3 concentrations in both sparsely and densely populated regions. In particular, 6 major Chinese cities were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 59 publications
(43 reference statements)
2
79
0
Order By: Relevance
“…The variations of O 3 implied a different formation mechanism of O 3 pollution from the other four pollutants (R.‐J. Huang et al, 2014; W. Wang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The variations of O 3 implied a different formation mechanism of O 3 pollution from the other four pollutants (R.‐J. Huang et al, 2014; W. Wang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…To mitigate air pollution in this area, the Chinese government implemented “Law on the Prevention and Control of Atmospheric Pollution” in 2015. In addition, “2+26” cities were selected with critical strategies in 2017 (H. Li et al, 2018), which were designed to manage the primary‐fuel quality, combustion technology, and emission index for residents and industries (Tan et al, 2016; W. Wang et al, 2017). There is no time to delay to assess the risks arising by air pollution and to improve the air quality for human health.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, air pollution has become increasingly serious in China (Tang et al, 2012;Shi et al, 2014;Rohde and Muller, 2015), and it currently poses a grievous risk to human health (Wang and Mauzerall, 2006). Previous studies have indicated that air pollution has killed more people worldwide than tuberculosis, AIDS, breast cancer, and malaria (Yang et al, 2013;World Health Organization, 2014a, b).…”
Section: Introductionmentioning
confidence: 99%